Prognostic value of speckle tracking echocardiography-derived strain in unmasking risk for arrhythmias in children with myocarditis - Rolfs, Nele; Huber, Cynthia; Opgen-Rhein, Bernd; Altmann, Isabell; Anderheiden, Felix; Hecht, Tobias; Fischer, Marcus; Wiegand, Gesa; Reineker, Katja; Voges, Inga; Kiski, Daniela; Frede, Wiebke; et al. (Biomedicines, 2024)
Background/Objectives: Risk assessment in pediatric myocarditis is challenging, particularly when left ventricular ejection fraction (LVEF) is preserved. This study aimed to evaluate LV myocardial deformation using speckle-tracking echocardiography (STE)-derived longitudinal +strain (LS) and assessed its diagnostic and prognostic value in children with myocarditis. Methods: Retrospective STE-derived layer-specific LV LS analysis was performed on echocardiograms from patients within the multicenter, prospective registry for pediatric myocarditis "MYKKE". Age- and sex-adjusted logistic regression and ROC analysis identified predictors of cardiac arrhythmias (ventricular tachycardia, ventricular fibrillation, atrioventricular blockage III°) and major adverse cardiac events (MACE: need for mechanical circulatory support (MCS), cardiac transplantation, and/or cardiac death). Results: Echocardiograms from 175 patients (median age 15 years, IQR 7.9-16.5 years; 70% male) across 13 centers were included. Cardiac arrhythmias occurred in 36 patients (21%), and MACE in 28 patients (16%). Impaired LV LS strongly correlated with reduced LVEF (r > 0.8). Impaired layer-specific LV LS, reduced LVEF, LV dilatation, and increased BSA-indexed LV mass, were associated with the occurrence of MACE and cardiac arrhythmias. In patients with preserved LVEF, LV LS alone predicted cardiac arrhythmias (p < 0.001), with optimal cutoff values of -18.0% for endocardial LV LS (sensitivity 0.69, specificity 0.94) and -17.0% for midmyocardial LV LS (sensitivity 0.81, specificity 0.75). Conclusions: In pediatric myocarditis, STE-derived LV LS is not only a valuable tool for assessing systolic myocardial dysfunction and predicting MACE but also identifies patients at risk for cardiac arrhythmias, even in the context of preserved LVEF.